FEMALE INMATES: A NEGLECTED POPULATION IN MEDICAL POLICIES OF PAKISTAN - Muhammad Abdullah Avais; Aijaz Ali Wassan (Journal of University Medical & Dental College, 2017)
Abstract: Background: Medical health issues of female prisoners are neglected in the field of research in Pakistan. The main idea of a present research was to find out the health issues, and satisfaction toward provided health facilities to convicted women prisoners in Sindh and Punjab provinces. Methods: It was an exploratory study, and all convicted female inmates 133 from women prisons of Sindh (Karachi, Hyderabad and Larkana) and Punjab (Lahore and Multan) provinces were interviewed due to meager strength of inmates. The mean age of respondents were 28.76 years with SD + 8.80. The study was carried out from June 2015 to June 2016. Due to sensitivity of instant research neither name nor any identification of respondents was interrogated. The data was collected through interviews and official jail/medical record. All the respondents were generally briefed regarding study and interviews were conducted with their due consent. Results: It was observed that 83% respondents were not satisfied with the provided health facilities. 3.8% respondents were suffering from Hepatitis-C, 12.8% high blood pressure, 18.8% depression, and 3.8% tuberculosis. Conclusion: The convicted female inmates were suffering from different diseases. They were not satisfied with provided health facilities. Due to inadequate health facilities, malnutrition and presence of inmates with communicable diseases, there is likelihood that healthy inmates may suffer from different diseases. Although the government is trying to provide basic health facilities but there is need of more intention exclusively from policy makers. Abstract: The present research was aimed to explore the medical health issues and availability of medical health facilities for women prisoners in Sindh and Punjab provinces. All the convicted female inmates 133, from 3 prisons of Sindh (Karachi, Hyderabad and Larkana) and 2 of Punjab (Lahore and Multan) were interviewed due to meager strength of convicted inmates. The mean age of respondents was 28.76 with SD + 8.80. The results indicate that majority of respondents 81% were married, 54.1% illiterate and 72.9% respondents of rural regions. Per month family income of 42.9% respondents were between 6,000 – 10,000 rupees. 37.7% respondents tried to commit suicide. 32.3% respondents faced physical and 6.8% sexual violence in their childhood. 55.6% respondents were not satisfied with provided health facilities and 62.4% were not satisfied with provided food in prisons. 3.8% respondents were suffering from Hepatitis-C, 12.8% high blood pressure, and 3.8% tuberculosis. 68.4% respondents shared that their place of imprisonment has not sufficient light facility and 67.3% shared that their place of imprisonment is not airy. Therefore, the government should review the medical policies for female inmates and their place of imprisonment must be airy and lighted enough.